Will the Brazilian Federal Supreme Court reinstate the Convention no. 158 of the International Labor Organization (ILO) in the Brazilian legal order? On a possible turnaround, through international law, of Brazilian labor laws - Borges, Daniel Damasio [UNESP] (Centro de Ensino Unificado de Brasilia, 2018)
The Convention n. 158 concerning Termination of Employment at the Initiative of the Employer regulates a very controversial matter: the limits that are imposed on free enterprise in order to protect employment. These discussions about the legal meaning of the Convention 158 may be revived when the Brazilian Supreme Court concludes its judgment about the constitutionality of the denunciation of this treaty. In fact, most judges seem to consider the denunciation unconstitutional. If this judgment is confirmed, this will mean the re-entry into force of the Convention 158. This paper discusses the legal effects of this reentry into force. In our study, we use bibliographical review, with a special reference to comparative law, and the reports of the ILO bodies which supervise the application of the Convention 158. In particular, two legal rights arise from the Convention: a) the right of the employees to not be dismissed without a valid reason; and b) the right of the employees to be consulted, through their representatives, before collective dismissals. This paper analyses how these rights should be interpreted by the Brazilian domestic jurisdictions and highlights the contribution of the Convention 158 to the effective protection of employment in Brazilian law.
E se o Supremo Tribunal Federal (STF) restabelecer a vigência da Convenção n. 158 da Organização Internacional do Trabalho (OIT) na ordem jurídica brasileira? Sobre uma possível reviravolta, pela via do direito internacional, das leis trabalhistas brasileiras
Keywords: Employment protection; Fundamental social rights; International Labour Organization; Treaty denunciation